대학생 문제도박의 성별 차이와 건강위험행동과의 관련성 - 김영호(Young-Ho Kim) (保健敎育健康增進學會誌, 2011)
Objectives: This study aims to identify differences in problem gambling among Korean university students by gender and to analyze the relationship between problem gambling and health risk behaviors. Methods: With a sample of 2,026 4-year university students, a questionnaire included CPGI (Canadian Problem Gambling Index) scale and health risk behavior items was administered. Descriptive statistics, t-test, and ANOVA were performed on the data. Results: The prevalence of gambling addiction of male students(14.6%) was two times higher than that of female students(6.6%). The severity of problem gambling was higher in: smokers, those with drug use experience, heavy drinkers, and those with frequently recurring suicidal thoughts, respectively. Conclusions: This study suggests that the problem gambling of university students is a complicated and comprehensive public health problem that is related with health risk behaviors such as alcohol drinking, smoking, drug use, and suicidal thoughts. Prevention strategies and policies are suggested based on the study results.